Molecular Subclassification Based on Crosstalk Analysis Improves Prediction of Prognosis in Colorectal Cancer - Liu, Xiaohua; Su, Lili; Li, Jingcong; Ou, Guoping (Frontiers in Genetics, 2021)
The poor performance of single-gene lists on prognosis predicting in independent cohorts have limited its clinical usage. Here, we employed a pathway-based approach that embedded biological features were aiming to export reproducible features. Based on the pathway activity score, sure independence screening, and K-means clustering analyses, the colorectal cancer patients were clustered into G2 (aggressive) and G1 (moderate) subgroups. The differences between the two groups were compared at levels of survival, somatic mutation, pathway activity, and tumor infiltrated immunocytes, and revealed that the survival outcome of the G2 group was less good than G1 subgroup, and the mutation burden rates of oncogenes, such as HRAS, DCLK1, and EPHA5 were significantly higher in G2 than G1 subgroups; similarly, the enhanced activity of critical pathways might also be driver causes leading to the progression of colorectal cancer. Taken together, we establish a novel prognostic classification system, which offers meritorious insights into the hallmarks of colorectal cancer.